Cationic Lipid Modification of Nuclear Hormone Receptor-Ligands: A Strategy for Developing a New Class of Targeted Anticancer Therapeutics - Yousuf, Md; Banerjee, Rajkumar (Current Indian Science, 2024)
Ubiquitous expression patterns of nuclear hormone and their receptors (NHRs) have their own roles in performing essential functions in controlling hormone responsive element-promoted gene transcription. In diseased states such as cancer, NHRs play crucial roles and hence targeting these receptors are essential as it gives us a window of opportunity for developing targeted anticancer therapeutics. In comparison to traditional chemotherapy drugs, targeted therapeutic drugs are hypothetically advantageous in terms of efficacy and safety and hence the idea of developing such targeted drugs are inclined to become a mainstream cancer treatment option. This review selectively compiles data regarding NHR-targeting, while majorly focusing on cancer treatment using anticancer small molecules and/or nanotherapeutics targeting estrogen receptor, progesterone receptor, glucocorticoid receptor, and vitamin D receptor. In this study, we selectively emphasized on estrogen receptor. Herein, we mainly highlight the strategy of lipid-modification to convert respective receptor ligands into NHR-targeted anticancer molecules as well as nanotherapeutics. We focused on the strategy of chemical conjugation of those ligands with twin-aliphatic carbon chain-based cationic lipids. The strategy successfully led to the development of a new class of anticancer therapeutics. These are either small-molecule anticancer agents or self-aggregating nanotherapeutics. In spite of great anticancer output, the concept of NHR-targeted anti-cancer therapy still needs to overcome further hurdles before those are projected for clinical settings.
Keywords: Cationic lipid